THE EFFECT OF AL-QUR'AN MURATTAL AUDIO ON THE STUDENTS’ MEMORY OF BIOLOGICAL LATIN NAMES IN HUMAN MOVEMENT SYSTEM MATERIALS IN GRADE XI IPA SMA IT WAHDAH ISLAMIYAH - Ulfiani Rahman; Muslimah S. Waskita; Hamansah Hamansah (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
This study aims to: (1) Describe the level of memory ability of biological Latin names of human motion system material in students who listened to murattal audio, (2) Determine the level of memory ability of biological Latin names of human motion system material of students who did not listen to murattal audio, (3). Analyze the influence of murattal audio on the memory of biological Latin names in the human motion system material. This research was quasi-experimental with a non-equivalent control group design. This study involved 58 of 70 students consisting of 29 students in a control class and 29 students in an experimental class. They were selected by the purposive sampling technique. The research instrument was a learning outcome test. The data were analyzed through descriptive statistical analysis and inferential analysis which were preceded by prerequisite tests and then carried out by an independent sample t-test. The results showed that the memory ability of biological Latin names in the experimental class is higher than in the control class. Furthermore, the experimental class is in the high category, while the control class is in the medium category. Thus, it proves that the murattal audio of Al-Qur'an can improve students’ memory of biological Latin names. Research implications are also presented in this study.